Dissecting the temporal requirements for homeotic gene function. - Castelli-Gair, J.E.; Greig, S.; Micklem, G.; Akam, M.E. (Development, 1994)
Homeotic genes confer identity to the different segments of Drosophila. These genes are expressed in many cell types over long periods of time. To determine when the homeotic genes are required for specific developmental events we have expressed the Ultrabithorax, abdominal-A and Abdominal-Bm proteins at different times during development using the GAL4 targeting technique. We find that early transient homeotic gene expression has no lasting effects on the differentiation of the larval epidermis, but it switches the fate of other cell types irreversibly (e.g. the spiracle primordia). We describe one cell type in the peripheral nervous system that makes sequential, independent responses to homeotic gene expression. We also provide evidence that supports the hypothesis of in vivo competition between the bithorax complex proteins for the regulation of their down-stream targets.